Long dark road : Bill King and murder in Jasper, Texas - Ainslie, Ricardo C. (University of Texas Press, 2004)
"On a long dark road in deep East Texas, James Byrd Jr. was dragged to his death behind a pickup truck one summer night in 1998. The brutal modern-day lynching stunned people across America and left everyone at a loss to explain how such a heinous crime could possibly happen in our more racially enlightened times. Many eventually found an answer in the fact that two of the three men convicted of the murder had ties to the white supremacist Confederate Knights of America. In the ex-convict ringleader, Bill King, whose body was covered in racist and satanic tattoos, people saw the ultimate monster, someone so inhuman that his crime could be easily explained as the act of a racist psychopath. Few, if any, asked or cared what long dark road of life experiences had turned Bill King into someone capable of committing such a crime." "In this account of the murder and its aftermath, Ricardo Ainslie builds an unprecedented psychological profile of Bill King that provides the fullest possible explanation of how a man who was not raised in a racist family, who had African American friends in childhood, could end up on death row for viciously killing a black man. Ainslie draws on exclusive in-prison interviews with King, as well as with Shawn Berry (another of the perpetrators), King's father, Jasper residents, and law enforcement and judicial officials, to lay bare the psychological and social forces - as well as mere chance - that converged in a murder on that June night. Ainslie delves into the whole of King's life to discover how his unstable family relationships and emotional vulnerability made him especially susceptible to the white supremacist ideology he adopted while in jail for lesser crimes." "Long Dark Road not only answers the question of why such a racially motivated murder happened in our time, but it also offers a frightening, cautionary tale of the urgent need to intervene in troubled young lives and to reform our violent, racist-breeding prisons. As Ainslie concludes, far from being an inhuman monster whom we can simply dismiss, "Bill King may be more like the rest of us than we care to believe.""--Jacket.